Functional Connectivity Within the Gustatory Network Is Altered by Fat Content and Oral Fat Sensitivity – A Pilot Study - Frank-Podlech, Sabine; Heinze, Jaana M.; Machann, Jürgen; Scheffler, Klaus; Camps, Guido; Fritsche, Andreas; Rosenberger, Melanie; Hinrichs, Jörg; Veit, Ralf; Preissl, Hubert (Frontiers in Neuroscience, 2019)
Background: The amount of fat in ingested food leads to specific activation patterns in the brain, especially in homeostatic and reward related areas. On a behavioural and sensory level, the sensitivity to the oral perception of fat is associated with differential eating behavior and physiological parameters. Objective: We aimed to investigate the association between fat-dependent neuronal functional connectivity patterns and oral fat sensitivity. Background: The amount of fat in ingested food dictates specific activation patterns in the brain, particularly in homeostatic and reward-related areas. Taste-specific brain activation changes have also been shown and the sensitivity to the oral perception of fat is associated with differential eating behavior and physiological parameters. The association between oral fat sensitivity and neuronal network functions has, however, not yet been defined. Objective: We aimed to investigate the association between fat-dependent neuronal functional connectivity patterns and oral fat sensitivity. Design: To investigate the underlying changes in network dynamics caused by fat intake, we measured resting-state functional connectivity in 11 normal-weight male participants before and after a high- vs. a low-fat meal on two separate study days. Oral fat sensitivity was also measured on both days. We used a high-resolution functional magnetic resonance imaging sequence to measure any connectivity changes in networks with the seed in the brainstem (nucleus tractus solitarii, NTS), in homeostatic (hypothalamus) and in reward regions (ventral and dorsal striatum). Seed-based functional connectivity (FC) maps were analyzed using factorial analyses and correlation analyses with oral fat sensitivity were also performed. Results: Regardless of fat content, FC between NTS and reward and gustatory areas was lower after ingestion. Oral fat sensitivity was positively correlated with FC between homeostatic regions and limbic areas in the high-fat condition, but negatively correlated with FC between the dorsal striatum and somatosensory regions in the low-fat condition. Conclusions: Our results show the interaction of oral fat sensitivity with the network based neuronal processing of high- vs. low-fat meals. Variations in neuronal connectivity network patterns might therefore be a possible moderator of the association of oral fat sensitivity and eating behavior.